A Domestic Air Demand Analysis System Considering Oligopoly Condition - ISHICURA, Tomoki (INFRASTRUCTURE PLANNING REVIEW, 2007)
Airline's behavior in the market is an exogenous condition in the existing “practical” air demand forecast models. However domestic air transport market is competitive nowadays and airlines can almost freely choose their strategies. Policymaker therefore needs to estimate how aviation policy influences not only passenger's behavior but also airline's behavior. This paper proposes a model which integrates an oligopoly market model and a demand flow assignment model to analyze policy alternatives in above situation.